(untitled) (Revista de História da UEG (REVHIST), 2020)
This article seeks to think about the trajectory of a visual image within a set that integrates the problems of photographic images in a contemporary colonial context. For this, it travels through the meanings attributed to a photograph produced in the first Portuguese Colonial Exhibition of the child named of Augusto. Its social circuit was intense and marked by different consumption spaces, persisting today in the circuit of collectors of colonial objects. Therefore, the itinerary presented allows to outline some uses and functions performed by the technical image in the Portuguese colonial context and to address some important issues for the development of historical studies with photography in contemporary colonialism. .Keywords: Photography. Colonialism. Social circuit. Visuality.